Heating Analysis Of Used Cooking Oil Refining Equipment Using Activated Charcoal With A Heating Element Capacity Of 20 Liters / Process - Fahmi Al Diansyah; Anwar Ilmar Ramadhan; Firmansyah Firmansyah; Mohd Amiruddin Fikri (Faculty of Engineering Universitas Muhammadiyah Jakarta, 2023)
Cooking oil that is used repeatedly is very harmful to health. The use of cooking oil repeatedly and continuously in the frying process will result in a degradation reaction, thereby reducing the quality of the cooking oil. Therefore, the purification of used cooking oil needs to be done with the aim of making use of consumable oil and to reduce the risks that can endanger health if using used oil repeatedly. The purpose of this research is to find out the heat energy produced by the band heater during the refining process of used cooking oil with activated charcoal. Knowing the effect of band heater power on the heating time of used cooking oil in the refining process. Changing the ratio of oil composition to activated charcoal to visual purification results. This research method uses a comparison between testing with numerical simulations using Ansys. Based on research, it is known that the greater the heating power used, the less time it takes to heat the oil up to 100oC, the time needed for the process of refining used cooking oil is the fastest, namely for 2 hours 30 minutes with a composition of 80%: 20% with the heat flux used 5500 W/m2, and which required a longer time of 4 hours 45 minutes with a composition of 60% : 40% with the heat flux used 3500W/m2. Visually, the best purification results were obtained, namely with a composition of 70% used cooking oil and 30% activated charcoal with a yellow-orange color, while visually the poorer results were obtained with a composition of 80% used cooking oil and 20% activated charcoal with a reddish yellow color. Thus the composition ratio between used cooking oil and activated charcoal affects the results of the refining process, where visually the best composition ratio is 70% used cooking oil and 30% activated charcoal with a stirring speed of 120 rpm. The highest percentage of free fatty acid (BA) reduction in this study was 73.05% and the highest percentage of peroxide value (PV) reduction was 56.88%.